Influence of fatty acid methyl ester composition on tribological properties of vegetable oils and duck fat derived biodiesel. (September 2017) - Hamdan, S.H.; Chong, W.W.F.; Ng, J.-H.; Ghazali, M.J.; Wood, R.J.K.
Abstract: To explore its potential as a biolubricant/additive, the study determines the frictional properties at various lubrication regimes for biodiesels derived from vegetable oils, hydrogenated vegetable oil and animal fat. It is found that the frictional characteristics for the biodiesels can be divided into Group I (feedstocks from winter crops) and Group II (feedstocks from summer crops, animal fat and hydrogenated vegetable oil). For each of the groups, with decreasing ratio of mono-unsaturated to total saturated fatty acid methyl ester content, the biodiesels' friction force reduces while their load carrying capacity deteriorates. From the experimental results, it is deduced that soybean biodiesel shows great potential as a biolubricant/additive because it possesses low friction force with the highest possible load carrying capacity. Highlights: Biodiesel lubricity trends can be divided into two melting temperature groups. Friction modifier effect and load carrying capacity are mapped on a ternary plot. From the tested biodiesels, soybean biodiesel shows best potential as biolubricant.